2012
DOI: 10.1186/1471-2334-12-55
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of severe pediatric adenovirus lower respiratory tract infections in Manitoba, Canada, 1991-2005

Abstract: Background Most pediatric adenovirus respiratory infections are mild and indistinguishable from other viral causes. However, in a few children, the disease can be severe and result in substantial morbidity. We describe the epidemiologic, clinical, radiologic features and outcome of adenovirus lower respiratory tract infections (LRTI) in Aboriginal and Non-Aboriginal children in Manitoba, Canada during the years 1991 and 2005. Methods This was a retrospective study of 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
48
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 28 publications
9
48
0
3
Order By: Relevance
“…Serotype 1-3 have shown predominance in pediatric adenovirus lower respiratory tract infection in Canada [2] and in our study, 2 pediatric cases of LRTI were found to be associated HAdV-3. Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Serotype 1-3 have shown predominance in pediatric adenovirus lower respiratory tract infection in Canada [2] and in our study, 2 pediatric cases of LRTI were found to be associated HAdV-3. Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Therefore, it is of great importance to decipher the clinical and molecular characteristics of HAdV. Although many studies have been published (2,5,18), data on the molecular epidemiology of HAdV in tropi- Table 1 : Synonymous mutation was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a variety of genome types can be identified by the restriction fragment length polymorphism (RFLP) technique (6). Temporal and geographical distributions of serotypes and genome types have been reported (2,5,(7)(8)(9)(10)(11)(12). It has also been indicated that the emergence or switching of serotypes and genome types can cause HAdV outbreaks (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de esta limitación el dato coincide con lo reportado en la literatura, especialmente con relación a la relevancia del adenovirus en la causalidad de la bronquiolitis obliterante post-infecciosa. 15,16 En cuanto al pronóstico de la enfermedad y con un seguimiento promedio de 5.6 años, obser-vamos una evolución global desfavorable en el 71% de los casos. Nuestros pacientes tuvieron consultas y hospitalizaciones frecuentes (a veces con necesidad de ventilación mecánica) y requirieron numerosos estudios paraclínicos entre ellos tomografía de tórax, gammagrafías pulmonares, estudios inmunológicos, electrolitos en sudor, ecocardiogramas y polisomnografías.…”
Section: Discussionunclassified